Efficacy and safety of secukinumab for moderate to severe plaque psoriasis in children: A report of 10 cases - FU Tao; ZHU Liang; GAO Yonglei; XIE Fang; FAN Menghong; WANG Kun; XIA Ke; CHEN Tao; LIU Chunxi; JIANG Dou (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To study the efficacy and safety of secukinumab in the treatment of moderate and severe plaque psoriasis in children. Methods A total of 10 children with psoriasis were enrolled at Yongcheng Central Hospital from November 2021 to November 2022. All patients were treated with subcutaneous injection of secukinumab and followed up for 52 weeks. The psoriasis area and severity index (PASI) and childrens' dermatology life quality index(CDLQI) were evaluated, and adverse reactions were observed. Results After 4 weeks of the treatment, 8 patients achieved PASI 75, among which 7 patients achieved PASI 90 and PASI 100 was observed in 5 patients. After 8 weeks of the treatment, all 10 patients reached PASI 75, including 8 patients with PASI 100. After 12 weeks, all 10 patients achieved PASI 100. By 52 weeks, 9 patients reached PASI 75, including 8 patients with PASI 90 and 7 patients with PASI 100. After 4 weeks of the treatment, CDLQI scores were significantly decreased and declined to 0 by 52 weeks. No adverse reactions were observed in all patients. Conclusions Secukinumab can rapidly improve moderate to severe plaque psoriasis in children and exhibits long-lasting benefit. It is safe and can quickly improve the quality of life of the children.